2015
DOI: 10.12968/jowc.2015.24.6.268
|View full text |Cite
|
Sign up to set email alerts
|

Using transparent polyurethane film and hydrocolloid dressings to prevent pressure ulcers

Abstract: The results suggest that the transparent polyurethane film had a better performance and was more effective than the hydrocolloid dressing in preventing PU development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 16 publications
1
26
0
3
Order By: Relevance
“…The most common study design was RCTs ( n = 6). Regarding the PU preventive interventions, most of the featured studies focused on support surfaces, health professional's education, multiple intervention programmes, repositioning and early mobilisation, preventive skincare, prophylactic dressings, remind systems on patient care plan, and risk‐assessment tools . According to the care setting where the studies were carried out, most of them ( n = 17) were developed in intensive care units (ICU) followed by medicine ( n = 6), geriatrics ( n = 2), surgical ( n = 2), orthopaedics ( n = 2), oncology ( n = 1), rehabilitative ( n = 1), community hospital ( n = 1), and other specific units ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common study design was RCTs ( n = 6). Regarding the PU preventive interventions, most of the featured studies focused on support surfaces, health professional's education, multiple intervention programmes, repositioning and early mobilisation, preventive skincare, prophylactic dressings, remind systems on patient care plan, and risk‐assessment tools . According to the care setting where the studies were carried out, most of them ( n = 17) were developed in intensive care units (ICU) followed by medicine ( n = 6), geriatrics ( n = 2), surgical ( n = 2), orthopaedics ( n = 2), oncology ( n = 1), rehabilitative ( n = 1), community hospital ( n = 1), and other specific units ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…Among all the studies that assessed dressings as a PU preventive measure ( n = 6), there was at least one type of dressing that showed a statistically significant decrease in incidence rates of PU occurrence. The study conducted by Dutra et al showed that polyurethane film dressings were more effective than hydrocolloid dressings in decreasing PU incidence in the trochanteric and sacral areas for patients cared for in the ICU, coronary unit, and in one general medicine unit . Other studies found that a multilayered silicone foam dressing was effective in reducing PUs on heels and sacrum in orthopaedics patients and patients in ICU when previously applied in emergency department or within 24 hours of admission to the ICU .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Care must be taken to remove these dressings as they can rip skin if removed forcefully. 51 Negative pressure wound therapy. Negative pressure wound therapy (NPWT) consists of a foam dressing, which can be tailored to fit the patient's wound and is covered by a transparent film to enable creation of a vacuum in the wound when the foam is attached to a suction device via tubing.…”
Section: Dressings and Topical Agentsmentioning
confidence: 99%
“…Biodegradable elastomeric polyurethane has been used for biomedical applications due to its tunable mechanical properties, processability, biodegradability, and good biocompatibility . It has been processed into films, electrospun fibers, and porous scaffold, for tissue engineering application as well as nano/micro particulates, membranes, and matrices for controlled drug release. The biodegradable polyurethane has also been combined with traditional conductive polymers or organic additives to form PU‐based conductive composites for tissue engineering .…”
Section: Discussionmentioning
confidence: 99%